Phylogeography of three closely related myrmecophytic pioneer tree species in SE Asia: implications for species delimitation - Fiala, Brigitte; Slik, Ferry; Weising, Kurt; Maschwitz, Ulrich; Mohamed, Maryati; -, Jamsari; Guicking, Daniela (Springer, 2016)
Members of the Euphorbiaceae are ecologically important elements of Southeast Asian forests. Species of the pioneer tree genus Macaranga, which is also known for its association with ants, are often abundant in disturbed areas. Phylogenetic studies suggested a recent radiation of section Pachystemon which comprises the majority of obligate myrmecophytes within Macaranga. In the present study, we analyzed the genetic structure of three closely related species of this section (M. constricta, M. griffithiana, and M. motleyana) with the aim of resolving their controversial taxonomy and historical biogeography. Chloroplast DNA haplotypes proved to be species-specific and showed a strong phylogeographic pattern. Nuclear microsatellite data supported the taxonomic distinctness of M. griffithiana and M. motleyana, but gave ambiguous results for M. constricta. Genetic differentiation was stronger each within M. griffithiana and M. motleyana than between M. constricta and M. griffithiana, highlighting problems of defining species boundaries. We found no indication for introgression or hybridization events. The high intraspecific morphological variation of the Bornean endemic M. motleyana was partly reflected by similar patterns of genetic variation. The pronounced genetic structure indicates a comparatively long diversification for this species. In contrast, the weak genetic differentiation within M. griffithiana, as well as the widespread distribution of its most common chloroplast haplotype from peninsular Malaysia up to Indochina, indicates a recent expansion in this area. Despite their morphological similarity and close relatedness, all species possess their own specific ant-partners with a corresponding distribution pattern.